Mind the Gap: Hong Kong's Sexual Conviction Record Scheme. Issue 2 (9th December 2015) - ONG, Rebecca; SABAPATHY, Sandy; CHUI, Wing Hong
Abstract: It is likely that no criminal behaviour breeds as much condemnation and fear as sex offences. Tragic examples of young victims of sex offenders from around the world have raised societal concerns and prompted calls for increased surveillance and control. It is responsible public policy to address these concerns in ways that will increase public protection and allay unnecessary fears. The purpose of this paper is three-fold. First, the paper examines Hong Kong's recently implemented Sexual Conviction Record Check Scheme against the Territory's low crime victimization rate. Second, it compares the Scheme with pre-employment screening checks in Australia and the UK. The paper finally concludes with proposals for changes to the Scheme.